Does the Low-Intensity Laser Protocol Affect Tissue Healing After Third Molar Removal? - Bianchi de Moraes, Michelle [UNESP]; Gomes de Oliveira, Rúbia [UNESP]; Raldi, Fernando Vagner [UNESP]; Nascimento, Rodrigo Dias [UNESP]; Santamaria, Mauro Pedrine [UNESP]; Loureiro Sato, Fábio Ricardo [UNESP] (Elsevier, 2020)
Purpose: Studies have shown that laser therapy is a recommended therapy for improving the postoperative period in patients undergoing extraction of the third molars; however, there is still no definition regarding the best protocol to be used. The aim of this study was to measure and compare periodontal tissue healing using 2 different laser protocols. Materials and Methods: A double-blinded, randomized, prospective study with patients submitted to inferior third molar extraction was performed, with the sample divided into 3 groups according to the laser application protocol and followed for 6 months: group I, 10 J/cm2; group II, 30 J/cm2; and group III, sham. The primary variable was probing depth, and the secondary variables were trismus, facial edema, and pain. Results: The sample was composed of 57 patients: 19 in group I, 20 in group II, and 18 in group III. Analysis of the variables showed statistically significant differences between both groups that received laser therapy, with values of 1.46 for edema control on the third day and 0.54 on the seventh day in group I (P =.017) and 1.26 and 0.52, respectively, in group II (P =.001) compared with 0.59 and 0.49, respectively, in the sham group (P =.702), as well as a statistically significant difference for the 10-J/cm2 laser protocol for probing depth, with values of 7.58 mm preoperatively and 9.09 mm after 6 months (P =.013). Conclusions: The use of the low-intensity laser as adjuvant therapy after third molar extraction was more effective in the group undergoing the 10-J/cm2 laser protocol for improving periodontal tissue healing and in both laser therapy groups for reducing facial edema.